Impact of Perceived Severity of COVID-19 (SARS-COV-2) on Mental Health of University Students of Pakistan: The Mediating Role of Muslim Religiosity - Saleem, Muhammad; Bakar, Abou; Durrani, Areeha Khan; Manzoor, Zubair (Frontiers in Psychiatry, 2021)
Background: Perceived severity of COVID-19 (SARS-COV-2) is known to be associated with mental health of people in general and health professionals in particular in western societies. However, its association with the mental health of students in Pakistan, which is predominately a Muslim society, remains unclear so far. Moreover, the role of Muslim religiosity for such an association has not yet been investigated. This study aimed to examine the association and reports findings on impact of perceived severity on mental health with a sample of students from all five provinces of Pakistan. Methods: We did a cross-sectional online survey from 1525 Pakistani students in March 2020through standardized measurement tools. We then determined the prevalence of perceived severity among students and its impact on their mental health. The strength of associations between these variables was estimated using generalized linear models, with appropriate distribution and link functions. For the purpose, structural equation modeling through SmartPLS (3.0) software was utilized to analyze the results. Findings: The perceived severity of COVID-19 is significantly associated with mental health of Pakistani students, whereas, Muslim religiosity is strong mediator between perceived severity and mental health of Pakistani students. Conclusions: Though the perceived severity of COVID-19 is associated with mental health, this relationship can be better explained by the role of Muslim religiosity. When tested individually, the perceived severity accounted for only 18% variance in mental health that raised up to 57% by mediating role of Muslim Religiosity This difference clearly indicates the mediating role of Muslim religiosity in the association between perceived severity and mental health for Pakistani students.